2003
DOI: 10.1179/016164103101201463
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effect of recombinant tissue-plasminogen-activator (rt-PA) on edema formation in a large-animal model of intracerebral hemorrhage

Abstract: Hematoma puncture, fibrinolysis, and aspiration of the liquefied clot is a promising new treatment strategy for large intracerebral hemorrhages (ICH). Characteristics of the cellular injury and neuronal and glial cell death associated with ICH and the administration of fibrinolytic agents still need to be defined. We developed a porcine model to study the histopathological effects of recombinant tissue-Plasminogen-Activator (rt-PA) on perihematomatous cell integrity. In 20 pigs, lobar hematomas were induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 28 publications
1
26
1
1
Order By: Relevance
“…One is an autologous whole-blood model, and the other uses collagenase to induce intracerebral bleeding; both require stereotactic injections. The autologous whole-blood model is one of the earliest models used for the study of ICH in rats (Bullock et al, 1984;Nath et al, 1986;Wu et al, 2003), rabbits (Kaufman et al, 1985;Koeppen et al, 2004), dogs (Qureshi et al, 2001a;Steiner et al, 1975), and pigs (Thiex et al, 2003;Wagner et al, 1996), and has recently been adapted for use in mice (Lee et al, 2006;Nakamura et al, 2004b). It consists of whole blood drawn from the animal being injected directly into the cerebrum.…”
Section: Animal Models Of Intracerebral Hemorrhagementioning
confidence: 99%
“…One is an autologous whole-blood model, and the other uses collagenase to induce intracerebral bleeding; both require stereotactic injections. The autologous whole-blood model is one of the earliest models used for the study of ICH in rats (Bullock et al, 1984;Nath et al, 1986;Wu et al, 2003), rabbits (Kaufman et al, 1985;Koeppen et al, 2004), dogs (Qureshi et al, 2001a;Steiner et al, 1975), and pigs (Thiex et al, 2003;Wagner et al, 1996), and has recently been adapted for use in mice (Lee et al, 2006;Nakamura et al, 2004b). It consists of whole blood drawn from the animal being injected directly into the cerebrum.…”
Section: Animal Models Of Intracerebral Hemorrhagementioning
confidence: 99%
“…However, in our preliminary experiments, we found that the gender of piglets had no significant effect on the volume of hematoma, cellular damage determined by H&E staining and neurological deficits in piglets after ICH. In experimental studies using pigs, (Wagner et al 1996;Pourcyrous et al 1997;Thiex et al 2003), the either gender of animals were used. Accordingly, we used either gender of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The pig's large, gyrated brain, well-developed white matter, uniform health status, and relatively low cost make it an excellent large-animal model for ICH studies. The ability to use 20-to 30-fold larger ICH volumes in the pig compared with rodent species (Wagner et al 1996;Pourcyrous et al 1997;Thiex et al 2003) enables examination of surgical hematoma removal or clot aspiration. In addition, the greater white matter volume in large animals enables serum to accumulate and edema to develop adjacent to hematomas.…”
mentioning
confidence: 99%
“…tPA was also found to exacerbate brain edema thus leading to worsening of neurological outcomes in two types of brain injury unrelated to ischemia: brain trauma [115] and intracerebral hemorrhage [116,117]. A potential mechanism to explain the exacerbation of brain edema comes from stroke models and involves the action of tPA on the Blood Brain Barrier (BBB): it was shown that tPA can disrupt the BBB via LRP-mediated signaling to brain vascular endothelial cells.…”
Section: The Neurotoxicity Of Tpamentioning
confidence: 99%